Application of Diagnostic Veterinary Parasitology in the Management of Canine Helminthiasis: A Case Study from Depot Nigerian Army Veterinary Clinic, Zaria, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Gastrointestinal helminthic infections remain a major health concern in companion animals, with significant implications for animal welfare and zoonotic transmission. Accurate diagnosis through veterinary parasitology plays a critical role in the effective management and control of these infections. This report presents a case of mixed gastrointestinal helminthiasis in a dog, emphasizing diagnostic approaches, therapeutic management, and public health relevance. A two-year-old male Alsatian dog was presented to the Depot Nigeria Army Veterinary Clinic, Zaria, Nigeria, with diarrhoea, weight loss, and lethargy. Clinical examination revealed poor body condition and mild dehydration. Parasitological diagnosis using the faecal flotation technique revealed a mixed infection with Toxocara canis and Ancylostoma caninum. The dog was treated with fenbendazole (50 mg/kg orally for three consecutive days) alongside supportive rehydration therapy. Clinical recovery was observed within one week, with restoration of appetite and stool consistency. The successful management of this case reinforces the significance of accurate parasitological diagnosis, evidence-based anthelmintic therapy, and preventive strategies in controlling canine helminthic infections. Hence, there is a need to strengthen diagnostic capacity in veterinary clinics and promote One Health collaboration so as to contribute to improving animal health and reducing zoonotic risk in Nigeria.